Transcriptomic Analysis of Seed Coats in Yellow-Seeded Brassica napus Reveals Novel Genes That Influence Proanthocyanidin Biosynthesis - Hong, Meiyan; Hu, Kaining; Tian, Tiantian; Li, Xia; Chen, Li; Zhang, Yan; Yi, Bin; Wen, Jing; Ma, Chaozhi; Shen, Jinxiong; Fu, Tingdong; Tu, Jinxing (Frontiers in Plant Science, 2017)
Yellow seeds are a favorable trait for Brassica crops breeding due to better quality than their black-seeded counterparts. Here, we compared the Brassica napus seed coat transcriptomes between yellow- and brown-seeded near-isogenic lines (Y-NIL and B-NIL) that were developed from the resynthesized yellow-seeded line No. 2127-17. A total of 4,974 differentially expressed genes (DEG) were identified during seed development, involving 3,128 up-regulated and 1,835 down-regulated genes in yellow seed coats. Phenylpropanoid and flavonoid biosynthesis pathways were enriched in down-regulated genes, whereas the top two pathways for up-regulated genes were plant–pathogen interaction and plant hormone signal transduction. Twelve biosynthetic genes and three regulatory genes involved in the flavonoid pathway exhibited similar expression patterns in seed coats during seed development, of which the down-regulation mainly contributed to the reduction of proanthocyanidins (PAs) in yellow seed coats, indicating that these genes associated with PA biosynthesis may be regulated by an unreported common regulator, possibly corresponding to the candidate for the dominant black-seeded gene D in the NILs. Three transcription factor (TF) genes, including one bHLH gene and two MYB-related genes that are located within the previous seed coat color quantitative trait locus (QTL) region on chromosome A09, also showed similar developmental expression patterns to the key PA biosynthetic genes and they might thus potentially involved participate in flavonoid biosynthesis regulation. Our study identified novel potential TFs involved in PAs accumulation and will provide pivotal information for identifying the candidate genes for seed coat color in B. napus.